Widening the Methodological Lens on the Investigation of Diversity in the Transition to Higher Education: A Discussion - Gijbels, David; Esterhazy, Rachelle (Frontline Learning Research, 2021)
This discussion addresses the methodological approaches used in the special issue on student transitions and diversity. We provide an overview of how the different papers contribute to methodological development in the field, in particular by their use of advanced multi-factor analyses and accounting for diversity in student transitions at several levels. The discussion touches upon challenges concerning (a) the distinction of analytical levels, (b) different conceptualisations and operationalisations of diversity and (c) the types of data collection methodologies. We conclude by discussing future steps to widen the methodological lens in transition research.